The lncRNA ZFAS1 regulates lipogenesis in colorectal cancer by binding polyadenylate-binding protein 2 to stabilize SREBP1 mRNA - Huishan Wang; Yuli Chen; Yanwen Liu; Qiuhui Li; Jing Luo; Li Wang; Yuanyuan Chen; Chen Sang; Wen Zhang; Xianxiu Ge; Zhifeng Yao; Lin Miao; et al. (Elsevier, 2022)
Colorectal cancer (CRC) is the fourth leading cause of cancer-related mortality globally. Therefore, a better understanding of the early molecular events of this disease is needed. Long noncoding RNAs (lncRNAs) play a critical role in the regulation of tumorigenesis and cancer progression. In this study, we investigated the characteristics of ZFAS1 in CRC. We analyzed three independent microarray datasets of CRC tissues from GEO and found that ZFAS1 expression was remarkably upregulated in all three datasets. Moreover, we validated the overexpression of ZFAS1 in CRC tissues compared with normal tissues and found that ZFAS1 was positively correlated with tumor size and metastasis in CRC. Knockdown of ZFAS1 significantly suppressed the malignant phenotype and lipogenesis of CRC cells. Mechanistically, ZFAS1 binds polyadenylate-binding protein 2 (PABP2) to stabilize SREBP1 mRNA, thereby increasing the expression of SREBP1 and its target genes stearoyl-CoA desaturase (SCD1) and fatty acid synthase (FASN), thus promoting CRC lipid accumulation. These data demonstrated that ZFAS1 could act as an oncogene for CRC and that ZFAS1 reprograms lipid metabolism by binding with PABP2 to stabilize SREBP1 mRNA accumulation, implicating it as a novel and potent target for the treatment of CRC.